Performance of Mn-based H2S sorbents in dry, reducing atmosphere – Manganese oxide support effects. (15th May 2017) - Chytil, Svatopluk; Kure, Milly; Lødeng, Rune; Blekkan, Edd A.
Highlights: Additive effect observed for cerium supported manganese oxide due to H2 S sorption on the support as well as on the Mn oxide. Superior stability of zirconium supported Mn oxide in H2 . Strong metal oxide-support interaction influences the sorbent performance. Abstract: High temperature H2 S sorbents comprising manganese oxide (15 wt.%) supported on TiO2, ZrO2, CeO2 and Al2 O3 were prepared by wet impregnation using Mn(NO3 )2 ·4H2 O as Mn precursor. Upon activation in H2, the sorbent performance testing was conducted at 650 °C in a model gas mixture with a composition of 0.4 vol.% of H2 S in 40 vol.% of H2, the balance being inert gas. Sorbent regeneration was performed at 650 °C with 5.2 vol.% of O2 in N2 . The initial sorption performance is first reported for the parent (Mn-free) supports showing a considerable H2 S sorption on ZrO2 and CeO2 and a minor sorption on Al2 O3 and TiO2 . The Mn sorbents were subject to 13 sorption/regeneration cycles. The highest initial sorption capacity is reported for cerium supported Mn oxide, which is also the sample that deactivates most. A prolonged exposure to H2 at 650 °C results in a reversible loss of the sorption capacity that was observed for all the samples except for Mn on zirconia suggesting its superior stability in H2 . The supports, fresh and regenerated Mn sorbents were characterized by means of N2 sorption measurements, X-ray Diffraction and Raman spectroscopy. Temperature-Programmed Reduction was performed on the parent supports and fresh sorbents. The changes in material properties caused by the testing as well as a different degree of a metal oxide-support interaction influencing the sorption performance are discussed.